ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH PERSPEKTIF MANAJEMEN LIKERT DALAM MEWUJUDKAN KINERJA GURU DI SMP MUHAMMADIYAH 17 SURABAYA - Putri, Elsya Amelia; Amanah, Chimayatul; Fauziah, Nisaul; Saputra, Ilyas Adi; Khairunnisa, Melani Zahra; Roesminingsih, Erny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the principal’s leadership style from the perspective of Likert’s management system and its implementation in improving teacher performance at SMP Muhammadiyah 17 Surabaya. This research employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation studies. The research informants consisted of the former principal who served during the 2015–2019 period and teachers selected using purposive sampling techniques. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the principal demonstrated communicative, humanistic, democratic, disciplined, and participative leadership characteristics through two-way communication, humanistic guidance, motivation and appreciation, as well as teacher involvement in school decision-making processes. Based on Likert’s management system perspective, the principal’s leadership style was categorized as System 3 (consultative) with a tendency toward System 4 (participative). The implementation of this leadership style positively contributed to improving teacher performance, particularly in lesson planning, instructional implementation, work discipline, and teachers’ responsibility in carrying out educational duties. This study shows that Likert’s management system perspective can be used to map principal leadership styles more specifically within the context of Muhammadiyah-based schools and support teacher performance improvement through consultative and participative leadership practices